Praktik Greenwashing dalam ESG Disclosure pada Industri Minyak dan Gas Global: Systematic Literature Review - Ramadhan, M. Faalih Athoullah; Kirana DP, Rina Tjandra (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Environmental, Social, and Governance (ESG) disclosure was initially designed as a sustainability transparency instrument. However, in the global oil and gas industry, this reporting is highly vulnerable to manipulation into greenwashing practices. This study aims to dissect the anatomy of environmental reporting manipulation and the weaknesses of ESG standards through a Systematic Literature Review (SLR) approach. Utilizing the frameworks of Legitimacy, Stakeholder, and Signalling Theory, this study consolidates 25 previous literature articles to reveal how extractive corporations exploit the flexibility of reporting regulations. The results indicate that greenwashing is a systemic institutional pathology used as a delaying tactic for energy transition. Furthermore, the weakness of reporting standards and the dysfunction of external sustainability audits create information asymmetry that delegitimizes the green finance ecosystem. This study concludes that ESG reporting instruments require regulatory restructuring using strict quantitative metrics and independent environmental audits to restore authentic energy transition accountability.